2019
DOI: 10.3344/kjp.2019.32.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of needle type on intravascular injection in transforaminal epidural injection: a meta-analysis

Abstract: Background Lumbosacral transforaminal epidural injection (TFEI) is an effective treatment for spinal disease. However, TFEI may have several types of complications, some of which can be attributed to intravascular injection. We reviewed studies to compare the intravascular injection rate among different needle types. Methods We searched the literature for articles on the intravascular injection rate among different needle types used in TFEI. The search was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…In the previous studies, blunt tip needle and pencil type needle have benefits in reducing the incidence of vascular injection during lumbar TFEI, compared with Quincke needle. [ 11 13 ] Whitacre needle and blunt tip needle have similar risk of intravascular injection during lumbar TEFI. [ 21 ] Whitacre needle has a tapering pencil-point tip and side hole, which can slide by the vessel without penetration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the previous studies, blunt tip needle and pencil type needle have benefits in reducing the incidence of vascular injection during lumbar TFEI, compared with Quincke needle. [ 11 13 ] Whitacre needle and blunt tip needle have similar risk of intravascular injection during lumbar TEFI. [ 21 ] Whitacre needle has a tapering pencil-point tip and side hole, which can slide by the vessel without penetration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] It was shown that the incidence of intravascular injection was significantly lower in Whitacre needle, compared with Quincke needle during lumbar TEFI (5.4% vs 16.2%). [ 13 ] However, it is not clear that which type of needle is better to reduce intravascular injection. It was reported that blunt needle is more beneficial than sharp needle during TEFI (2.4% vs 13.3%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown superiority of one needle type for specific procedures with respect to outcomes such as epidural contrast spread, fluoroscopy time, and complication rates, such as intravascular injection. [24][25][26][27] We maintain that in the hands of a trained proceduralist, spinal injections are safe and effective, and needle choice remains at the discretion of the performing physician based on comfort and technique.…”
Section: Injection Needlesmentioning
confidence: 99%